The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/d7020105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity of Two Mangrove Species with Morphological Alterations in a Natural Environment

Abstract: Mangrove is an ecosystem subjected to tide, salinity and nutrient variations. These conditions are stressful to most plants, except to mangrove plants that are well-adapted. However, many mangrove areas have extremely stressful conditions, such as salt marshes, and the plants nearby usually present morphological alterations. In Sepetiba Bay, two species of mangrove plants, Avicennia schaueriana and Laguncularia racemosa, have poor development near a salt marsh (SM) compared to plants at the riverside (RS), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Lira‐Medeiros et al () reported epigenetic differences in morphologically contrasting populations (1.9–7.5 m) of Laguncularia racemosa. Also, genetic differences using AFLP markers were reported among salt marsh and riverside A. schaueriana (Lira‐Medeiros, Cardoso, Fernandes, & Gomes‐Ferreira, ). Nevertheless, to date, no studies have considered the physiognomic type of R. mangle mangrove, environmental variables, or ecological characteristics of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Lira‐Medeiros et al () reported epigenetic differences in morphologically contrasting populations (1.9–7.5 m) of Laguncularia racemosa. Also, genetic differences using AFLP markers were reported among salt marsh and riverside A. schaueriana (Lira‐Medeiros, Cardoso, Fernandes, & Gomes‐Ferreira, ). Nevertheless, to date, no studies have considered the physiognomic type of R. mangle mangrove, environmental variables, or ecological characteristics of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset was cleaned by excluding loci with high amounts of missing data. The binary matrix created was used in Hickory v-1.1 [42], which is a Bayesian method that calculates deviation of the Hardy-Weinberg equilibrium by the Markov chain Monte Carlo (MCMC), so it does not calculate using allele frequency (details in [41]). The Bayesian differentiation index, θ ST , was calculated with the f -free model: 250,000 runs and 50,000 burn-ins in the Hickory software.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA extraction followed the protocol of Lira-Medeiros et al [41]. After the extraction, the samples were checked and quantified using 1% agarose gel and Nanodrop TM 2000 (Thermo Fisher Scientific, Waltham, MA, USA), then diluted into 12.5 ng/µL.…”
Section: Dna Isolation and Pcr Amplificationmentioning
confidence: 99%
“…Morphological markers are limited in number; their expression is often influenced by environment fluctuation, and many of them are not closely linked with economic traits and even have adverse effects on the development and growth of plants. However, morphological markers have been used for diversity analysis in various plant species (Lira-Medeiros et al 2015).…”
Section: Morphological Markersmentioning
confidence: 99%